Fiscal policy in unionized labor markets - Silvia Ardagna (Wellesley College, Department of Economics, 2002)
This paper investigates the effects of fiscal policy on economic activity, welfare, income distribution, and public finances in a dynamic general equilibrium model with a unionized labor market. The paper shows that increases to public employment, wages of public sector employees, unemployment benefits, and labor taxes put pressure on unions' wage claims, leading to higher private sector wages, lower employment and output. The paper also suggests that capitalists benefit from fiscal adjustments, while workers are hurt, especially during the stabilization and in its immediate aftermath. However, both capitalists and workers are better off when the adjustment is achieved by cutting welfare spending and the government wage bill. These types of fiscal consolidations are also the most effective in reducing the primary deficit and public debt.
Keywords: 330; Gewerkschaftsmitgliedschaft; Finanzpolitik; Arbeitsmarkt; Dynamisches Gleichgewicht; Theorie; OECD-Staaten